Human Parahippocampal Cortex Supports Spatial Binding in Visual Working Memory. (15th September 2017) - Dundon, Neil Michael; Katshu, Mohammad Zia Ul Haq; Harry, Bronson; Roberts, Daniel; Leek, E Charles; Downing, Paul; Sapir, Ayelet; Roberts, Craig; d'Avossa, Giovanni
Abstract: Studies investigating the functional organization of the medial temporal lobe (MTL) suggest that parahippocampal cortex (PHC) generates representations of spatial and contextual information used by the hippocampus in the formation of episodic memories. However, evidence from animal studies also implicates PHC in spatial binding of visual information held in short term, working memory. Here we examined a 46-year-old man (P.J.), after he had recovered from bilateral medial occipitotemporal cortex strokes resulting in ischemic lesions of PHC and hippocampal atrophy, and a group of age-matched healthy controls. When recalling the color of 1 of 2 objects, P.J. misidentified the target when cued by its location, but not shape. When recalling the position of 1 of 3 objects, he frequently misidentified the target, which was cued by its color. Increasing the duration of the memory delay had no impact on the proportion of binding errors, but did significantly worsen recall precision in both P.J. and controls. We conclude that PHC may play a crucial role in spatial binding during encoding of visual information in working memory.